Does Business Corruption Have To Be Considered in All Cases as Moral Misconduct? Two Statements - Linder , Christian; Linder , Rainer (Journal of Law and Governance, 2008)
In the fight against corruption, stringent punishments are imposed on corrupt companies. This paper questions whether these punishments are always wise or justified. Therefore, we distinguish between two kinds of corruption. The first one refers to corruption leading to personal enrichment, while the second type of corruption aims to increase the competitive ability of the company. In many countries – even if officially illegal – corruption and bribery are common while conducting business. Further, in many cases it is only the tip of the iceberg. The majority stay exempt from punishment. Thereby the second variant of corruption turns to be a vital competitive factor. In other words, companies which want to survive in the market are forced to conform to existing conventions. In markets where paying bribes is omnipresent, corruption is not a moral mistake but a free-market need. Therefore, the following questions arise: Where does the companies’ responsibility for corruption start and end? And, in which situation is it appropriate to punish companies for corrupt actions? In this paper, we discuss different corruption scandals involving Siemens, ABB and other competitors. Further we analyse country case studies from India and Russia. The result shows that corruption is in special cases a competitive requirement and not a lack of morality or honesty. It is argued that avoiding corruption in these circumstances cannot be considered the responsibility of companies. In addition, we show that to avoid corruption we need to take a closer look at the particular conditions in which companies “misbehave”. This paper adds a further perspective in the discussion on corruption.